Do Children with SLI Use Verbs to Predict Arguments and Adjuncts: Evidence from Eye Movements During Listening - Andreu, Llorenç; Sanz-Torrent, Mònica; Rodríguez-Ferreiro, Javier (Frontiers in Psychology, 2016)
Different psycholinguistic theories have suggested the importance of verb semantics in rapidly anticipating upcoming information during real-time sentence comprehension. To date, no study has examined if children use verbs to predict arguments and adjuncts in sentence comprehension using children with specific language impairment (SLI).Twenty-five children with SLI (aged 5 years and 3 months to 8 years and 2 months), twenty-five age-matched controls (aged 5 years and 3 months to 8 years and 2 months), twenty-five MLU-w controls (aged 3 years and 3 months to 7 years and 1 month), and 31 adults took part in the study. The eye movements of participants were monitored while they heard twenty-four sentences, such as El hombre lee con atención un cuento en la cama (translation: The man carefully reads a storybook in bed), in the presence of four depicted objects, one of which was the target (storybook), another, the competitor (bed), and another two, distracters (wardrobe and grape). The proportion of looks revealed that, when the meaning of the verb was retrieved, the upcoming argument and adjunct referents were rapidly anticipated. However, the proportion of looks at the theme, source/goal and instrument referents were significantly higher than the looks at the locatives. This pattern was found in adults as well as children with and without language impairment. The present results suggest that, in terms of sentence comprehension, the ability to understand verb information is not severely impaired in children with SLI.